Review of the Policy on Debt Limits in Fund-Supported Programs. (Policy Papers; Policy Paper ;, 2013)
This review examines the experience with the policy on debt limits in Fund-supported programs across the membership and proposes possible reforms to strengthen the policy. The policy was last reformed in 2009 with a view to adapting it to the changing circumstances in low-income countries (LICs). Given its primary focus on LICs, the reform left the policy applying to the rest of the membership broadly unchanged. The Fund's debt limits policy has been in place since the 1960s. From the policy's inception, concessional flows have been excluded from debt limits under the presumption that such financing was critical for LICs and posed only limited risks to debt sustainability. Over time, the exclusion of concessional flows has led to a bifurcation in the policy, with one branch focusing on members to whom concessional financing is normally available, and the other on those to whom it is not-a distinction which in practical terms has involved differentiating between LICs and non-LICs.